The Lingga Or Phallus At Kancing Gumi Temple As A Medium Of Worship For Hindus In Sulangai Village, Petang District, Badung Regency - I Ketut Tanu (Jayapangus Press, 2020)
There are many mediums used for worshipping in Indonesia. They can be in the form of ancient relics such as temples, statues, Pratima, or barongs. The aim is as a medium or means of concentrating one's mind on worshiping Ida Sang Hyang Widhi Wasa. One of the relics used as a means of worshipping is a Lingga or phallus. The lingga used as the research object in this study is the Lingga at the Kancing Gumi Temple. This temple is in Sulangai Village, Petang District, Badung Regency. This temple belongs to the Kahyangan Jagad Temple which is respected by the local community as a medium of worship. The Lingga at Kancing Gumi Temple is believed to be the key (kancing) for the stability of the island of Bali. This Temple is one of the temples that holds an important meaning in the cosmology-spiritual landscape in Bali. As the name suggests, this temple is the key that determines the stability of the island of Bali and even the world. Therefore, among the inhabitants of Sulangai Pura Village, it is believed that this temple is a lifeline or reinforce, a guardian of world stability. Kancing Gumi Temple is unique. There is a dresta (it is something prohibited to be done by everyone) for pemedek or everyone who wants to pray in this temple. Pregnant women and women who are breastfeeding are not allowed to come to this temple to pray. Besides, the pemedek is not allowed to offer pork. Moreover, the pemedek is prohibited to wear footwear in the area of ​​the Kancing Gumi Temple. If this prohibition is violated, it is believed that things that are not desirable will happen. This uniqueness is accepted and preserved as local assets by local inhabitants.